Marketing Communication dan Brand Awareness - Dominikus Tulasi (Bina Nusantara University, 2012)
The primary objective of marketing communications is to enhance brand equity as the means of moving customers to take favorable actions towards the brand—that is, trying it, repeat purchasing it and, ideally, becoming loyal towards the brand. Virtually, enhancing equity and affecting customer behavior depends on the effective use of all the marketing-mix elements. While, brand awareness relates to whether a brand name comes to mind when consumers think about a particular product category, and the ease with which that name is evoked. Brand awareness is the basic dimension of brand equity. From an indivual consummer’s perspective a brand has no equity unless the consummer is at least aware of the brand. Achieving brand awareness is the initial challenge for new brands, while maintaining high levels of brand awareness is an ongoing task for all established brands. As a matter of fact marketing communication can influence brand awareness when all tools of marketing mix performed optimally in its application.